Characterizing HOD in filaments and nodes of the cosmic web - Perez, Noelia Rocio; Pereyra, Luis A.; Coldwell, Georgina; Facundo, Rodriguez; Alfaro, Ignacio Germán.; Ruiz, Andrés Nicolás (Oxford University Press, 2024)
Impact Factor: 4.8